Governance in Family Business: A Literature Review - Ediriweera , Amali; Armstrong , Anona; Heenetigala , Kumi (Journal of Law and Governance, 2015)
Public and academic discussion on corporate governance and its related issues are clearly visible in any country with active capital markets. This suggests that good governance is a crucial factor for ensuring economic development. However, few studies can be found relating to non-listed or smaller firms. With the aim of contributing to this knowledge gap, this study reviewed the literature specific to corporate governance in family business in an emerging market, Sri Lanka, a small developing country with average lower middle income. The development of corporate governance best practices in Sri Lanka has been strongly affected by British models and systems, which derive from the Anglo- Saxon model of corporate governance. However, previous researchers who found that ownership of many listed companies was concentrated mainly in individual shareholders or a family concluded that family business in Sri Lanka is very critical to the economic development of the country. This study presents a review of non-listed and small to medium family business, and their two-tier mechanism of governing.